Illuminating the Marshall: novel techniques highlighted in an atrial tachycardia case report. Issue 4 (3rd August 2020) - Margato, Renato; Tampakis, Konstantinos; Albenque, Jean Paul; Combes, Stephane
Abstract: Background: Electroanatomic mapping is usually required in order to obtain a precise diagnosis and guide the ablation of atrial tachycardias (ATs) after ablation for atrial fibrillation (AF). However, epicardial connections may limit the interpretation of the endocardial activation sequence as well as the efficacy of endocardial radiofrequency ablation. Case summary: A 53-year-old man with history of AF ablation 2 years ago was admitted for ablation of a recurrent AT (cycle length 275 ms). Ultra-high-density mapping with the Rhythmia™ system revealed a challenging activation map with two focal points of early activation in the left atrium. The use of an advanced mapping software allowed the rapid reanalysis and reannotation of the activation map and suggested epicardial involvement of the Marshall bundle (MB). Subsequent ethanol infusion in the vein of Marshall (VOM) immediately terminated the tachycardia. Six months post-ablation, the patient had no recurrence of arrhythmias. Discussion: This case highlights the role of novel diagnostic and treatment methods in the management of a post-AF ablation AT. By developments in cardiac mapping systems, the rapid editing of a high-density activation map and clarification of the arrhythmia origin can be facilitated overcoming the limitations of conventional techniques. Moreover, ethanol infusion in the VOM was shown to be an effective alternative method in the management of MB-related tachycardias.